Gamification in English Learning: Strategies to Increase Student Motivation and Engagement in the Digital Age - Labibah, Hasna Fitri (Journal Corner of Education, Linguistics, and Literature, 2024)
This study aimed to analyze the application of gamification in English learning as a strategy to increase student motivation and engagement in the digital era. The research method used is a qualitative approach with data collection techniques such as observation, interviews, and documentation. The results show that gamification has a significant positive impact on the classroom atmosphere, learning motivation, and student participation. Through the implementation of game elements such as points, levels, badges, leaderboards, and quiz-based challenges, the learning atmosphere becomes more lively, fun, and interactive. Observations found that students were more enthusiastic in participating in learning activities, showed courage to speak English, and were more focused when facing mission-based challenges. Interviews with teachers revealed that gamification made it easier to monitor student progress while encouraging them to be more diligent in learning vocabulary, grammar, and speaking skills. Interviews with students also confirmed that they felt more motivated because the learning was similar to a familiar digital game. Documentation in the form of grade notes and activity reports showed an increase in student engagement and an increase in the average class score, especially in vocabulary mastery. Thus, it can be concluded that gamification is an innovative strategy that is effective in increasing student motivation, engagement, and learning outcomes in English learning in the digital era.